PELATIHAN FERMENTASI DEDAK PADI MENGGUNAKAN EM4 UNTUK PAKAN AYAM KAMPUNG - Emy Saelan; Sri Utami; Sulasmi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Rice bran is one of the feed ingredients that is cheap, easy to obtain and its availability does not compete with human needs. The nutritional content of bran is good enough to be used as animal feed, especially native chickens, but rice bran has a very high crude fiber content. The purpose of the Rice Bran Fermentation Training Using EM4 for Village Chicken Feed is to help farmers to provide cheap and quality feed ingredients with simple innovations through fermentation technology, improve livestock skills for processing feed ingredients, so as to reduce the dependence of farmers on commercial feed. The output to be achieved in this service activity is that farmers can make their own feed by means of fermentation for poultry, especially native chickens. The results obtained in this service show that livestock groups can provide fermented feed for poultry, especially free-range chickens, farmers are not dependent on commercial feed and increased production, especially meat and eggs, is increasing, so that farmers’ incomes become optimal.